Phytochemical, toxicity and antihyperglycaemic effects of Zea mays Linn leaves’ extracts - KOTIN, Lucrèce Mahoutin; ASSOGBA, Fidèle Mahoudo; AKAKPO, Huguette Baï; AHOUNOU AIKPE, Judith Fifamin; GODONOU, Jean-Benoît; DANSOU, Pierre Houndjovi; GBENOU, Joachim Djimon (Journal of Drug Delivery and Therapeutics, 2022)
In the Republic of Benin, several plants, including Zea mays Linn (Z. mays) are used for the treatment of diabetes without any scientific studies showing their effectiveness. The objective of this study is to investigate the effects of Z. mays leaves’ extracts on hyperglycaemic rabbits using the Oral Glucose Tolerance Test (OGTT), 2 g/kg of (D) + glucose and on hepatic glucose liberation. Phytochemical screening revealed that the plant leaves contain alkaloids, tannins, mucilage flavonoids, anthocyanin, leuco-anthocyanin, coumarins, heteroside, flavonoid, triterpenoids, steroids, reducing compounds, saponins, oses and holosides. Cytotoxity tests showed that the aqueous and ethanolic extracts were free of toxicity. The extracts have shown anti-hyperglycaemic activities dependent on specific dosage and timing. The effective dose is 500 mg/kg for the aqueous extract and for the ethanolic extract. The extracts are effective as compared with glibenclamide (reference product). Moreover, the ex vivo test conducted on the liver revealed that Z. mays aqueous extract inhibits the hepatic glucose liberation and 500 mg/kg is the most effective dose. The results of this study justify the traditional usage of the plant leaves under consideration in the treatment of diabetes. Key words: Zea mays extracts, phytochemical, hyperglycaemia, hepatic glucose, toxicity, Benin.